Ectomycorrhizal fungi mediate indirect effects of a bark beetle outbreak on secondary chemistry and establishment of pine seedlings. Issue 3 (1st June 2015) - Karst, Justine; Erbilgin, Nadir; Pec, Gregory J.; Cigan, Paul W.; Najar, Ahmed; Simard, Suzanne W.; Cahill, James F.
Summary Dendroctonus ponderosae has killed millions of Pinus contorta in western North America with subsequent effects on stand conditions, including changes in light intensity, needle deposition, and the composition of fungal community mutualists, namely ectomycorrhizal fungi. It is unknown whether these changes in stand conditions will have cascading consequences for the next generation of pine seedlings. To test for transgenerational cascades on pine seedlings, we tested the effects of fungal inoculum origin (beetle‐killed or undisturbed stands), light intensity and litter (origin and presence) on seedling secondary chemistry and growth in a glasshouse. We also tracked survival of seedlings over two growing seasons in the same stands from which fungi and litter were collected. Fungal communities differed by inoculum origin. Seedlings grown with fungi collected from beetle‐killed stands had lower monoterpene concentrations and fewer monoterpene compounds present compared with seedlings grown with fungi collected from undisturbed stands. Litter affected neither monoterpenes nor seedling growth. Seedling survival in the field was lower in beetle‐killed than in undisturbed stands. We demonstrate that stand mortality caused by prior beetle attacks of mature pines have cascading effects on seedling secondary chemistry, growth and survival, probably mediated through effects on below‐ground mutualisms.